(untitled) - Fisher, Charles A. (London, 1964)
The contemporary, economic, social and political problems of the islands of the South-West Pacific are described and analysed by an expert geographer.
Keywords: Southeast Asia,Đông Nam Á; Description and travel,Du lịch và mô tả